Gunfight on Europa Station - Boop, David (Baen, 2021)
The final frontier ain't so final in these 12 tales of space exploration and adventure: each a timeless yarn told around the warm glow of a nuclear reactor just before it goes supernova. There's a story for everyone who's ever dreamed of traveling the stars.